2018
DOI: 10.5792/ksrr.18.020
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Results and Risk of Patellar Injury between Attune and PFC Sigma Knee Systems

Abstract: PurposeThe purposes of this study were to compare clinical results after total knee arthroplasty (TKA) using the Attune and PFC Sigma knee designs and to investigate whether the use of the Attune prosthesis increased the risk of patellar injury in Asian patients.Materials and MethodsThree hundred knees that underwent TKA using Attune (group A) were compared to 300 knees that underwent TKA using PFC Sigma (group B). The Knee Society Knee Score (KS) and Function Score (FS), and range of motion (ROM) were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 23 publications
(33 reference statements)
0
25
0
Order By: Relevance
“…The mechanical axis (MA) was defined as the angle between the femoral and tibial mechanical axes on the orthoroentgenograms [9]. The positions of all femoral and tibial components were measured as the α, β, γ, and δ angles using the Knee Society radiographic evaluation method [10].…”
Section: Radiographic Evaluationmentioning
confidence: 99%
“…The mechanical axis (MA) was defined as the angle between the femoral and tibial mechanical axes on the orthoroentgenograms [9]. The positions of all femoral and tibial components were measured as the α, β, γ, and δ angles using the Knee Society radiographic evaluation method [10].…”
Section: Radiographic Evaluationmentioning
confidence: 99%
“…According to the authors, modifications to the patellofemoral joint did not result in significant Total randomized paƟents (n=200) AƩune (n=100); PFC Sigma (n=100) AƩune Exclusions (n=20) -PaƟent deceased (n=1) -Lost to follow up (n=12) -PaƟents refused their further parƟcipaƟon (n=7) PFC Exclusions (n=22) -PaƟent deceased (n=3) -Lost to follow up (n=14) -PaƟents refused their further parƟcipaƟon (n=5) AƩune followed for 2 years (n=80) PFC followed for 2 years (n=78) improvements. Song et al [12] showed more satisfactory results with the Attune TKA than the PFC regarding the KS, FS, WOMAC, and ROM after 2 years. In this study, a trend towards more favorable clinical results in the Attune group was detected with respect to ROM, KS and FS, however, without any statistical significance.…”
Section: Discussionmentioning
confidence: 97%
“…As the two TKA designs are amongst the most frequently used knee replacement systems worldwide, their clinical outcome is of great importance for orthopaedic surgeons [ 1 , 9 ]. The current literature suggests that both implants perform equally well, but well-designed, independent studies on the subject are required to clearly evaluate the effect of the implant design on the postoperative functional outcome [ 6 , 8 , 10 , 12 ]. This paper gives further insight into this evaluation as no prospective, randomized, controlled trial has yet been conducted to compare both designs.…”
Section: Introductionmentioning
confidence: 99%
“…Prominent designs such as the Attune Knee, which is a multi-radius trochlea groove design vs. the single radius trochlea groove PFC Sigma have shown excellent results in clinical studies [ 55 ]. The current literature provides inconsistent data regarding superiority of either design over the other [ 56 , 57 , 58 , 59 , 60 , 61 ]. This may be in line with the surgeons’ responses.…”
Section: Discussionmentioning
confidence: 99%